Differential electron emission in the ionization of Ne and Xe atoms under fast bare carbon ion impact - Biswas, Shubhadeep (2015)
Measurement of the energy and angular distributions of the double differential cross section (DDCS) of electron emission from Ne and Xe atoms in collision with 5 MeV u-1 bare carbon ions is reported. This study aimed to investigate the electron emission processes in the case of multi-electronic systems. In general, several clear differences between the electron emission spectra of Ne and Xe are found, which indicate the influence of the increasing number of electrons. For instance, the sharp peak due to the binary nature of collision is almost absent in the case of Xe, unlike Ne, which could be understood due to the increasing contribution from the strongly bound inner shell (such as) electrons for the Xe atom. The forward-backward angular asymmetry has also been derived from the angular distributions. For Xe, the qualitative behaviour of the asymmetry parameter is seen to be quite different since it reveals structures due to Auger contributions. It is, in general, different and much lower than that for Ne, which shows the smooth behaviour that one finds for other lighter atoms like He. The single differential and total cross sections are also derived. The theoretical calculations based on the prior form of the continuum distorted wave-eikonal initial state (CDW-EIS) approximation have been provided for both the targets. Overall, it gives a very good agreement with the energy and the angular distributions of DDCS for Ne. For Xe, the agreement is not as good as for Ne. We also provide a detailed discussion on the DDCS obtained from different sub-shell ionization, estimated in this framework.